DESIGN OF AN INDUSTRIAL PLANT FOR PRODUCTION OF MTBE IN KAZAKHSTAN - Aliyev, Asset; Baigarina, Assiya; Sauirbayeva, Assem; Madiyar, Bek; Shyntassov, Yernur; Baktybayeva, Amina (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This capstone project aims to design and simulate an efficient, cost-optimized MTBE production plant in Kazakhstan. The project scope encompasses the selection of an appropriate manufacturing pathway, determination of final product specifications, identification of suitable reaction kinetics and catalysts, design of major and minor equipment, selection of an optimal plant location, and comprehensive economic and market analyses. By integrating these elements, the project seeks to support Kazakhstan's transition towards sustainable energy practices while capitalizing on its existing resource base.
Keywords: type of access: open access